Ireland's great depression - Ahearne, Alan; Kydland, Finn; Wynne, Mark A. (Economic & Social Studies, 2006)
We argue that Ireland experienced a great depression in the 1980s comparable in severity to the better known and more studied depression episodes of the interwar period. Using the business cycle accounting framework of Chari, Kehoe and McGrattan (2005), we examine the factors that led to the depression and the subsequent recovery in the 1990s. We calculate efficiency, labour, investment and government wedges and evaluate the contribution of each to the downturn and subsequent recovery. We find that the efficiency wedge on its own can account for a significant portion of the downturn, but predicts a stronger recovery in output than occurred. The labour wedge also helps account for what happened during the depression episode. We also find that the investment wedge played no role in the depression.
An earlier version was presented at the Conference on Macroeconomic Perspectives in Honour of Brendan M. Walsh, held at University College Dublin on 7 October, 2005
Keywords: Depressions; Macroeconomics; Ireland; Economic policy